Hook modification to reduce rockfish and Pacific spiny dogfish bycatch in the U.S. West Coast Pacific halibut longline fishery - Dylan S. Heppell; Mark J. M. Lomeli; W. Waldo Wakefield; Bent Herrmann; Claude L. Dykstra; Ian J. Stewart (Reviews in Fish Biology and Fisheries, 2026)

Live-cell imaging reveals decreased cAMP in a PFE-associated c.1050-3C>G PTH1R cell model - K. Marnet; H. Subramanian; M. Wiesler; A. Borst; D. Liedtke; G. Pattappa; D. Docheva; V. O. Nikolaev; A. Stellzig-Eisenhauer; M. Eigenthaler; M. Herrmann (Journal of Molecular Medicine, 2026)
Primary failure of eruption (PFE) is a rare autosomal disorder provoked by heterozygous mutations in the parathyroid hormone receptor 1 ( PTH1R ) gene. PTH1R is a G protein-coupled receptor (GPCR) which regulates intracellular signaling molecules like cAMP. By using CRISPR/Cas9, the pathogenic PTH1R variant, c.1050-3C>G, was introduced into the periodontal ligament (PDL-hTERT) cell line to investigate molecular mechanisms in a PFE in vitro model. The PDL-hTERT immortal cell line, derived from human primary PDL cells, is a well-established model for dental diseases and expresses PTH1R . We performed different functional assays to compare the behavior of the PDL-hTERT WT versus PTH1R -mutated cells. cAMP synthesis and PKA activation were compared between different cell lines by live-cell imaging using Förster Resonance Energy Transfer (FRET)-based biosensors. Phosphorylation of VASP was measured to validate and compare the PKA activation between the cell lines. In summary, our experiments show that the mutated cell line has no major phenotypic changes, but the PTH1R downstream signaling cascade is impaired. Key messages A rare autosomal disorder linked to mutations in the PTH1R gene, which encodes a G protein-coupled receptor regulating intracellular signaling, including cAMP production. The pathogenic PTH1R mutation (c.1050-3C>G) was introduced into a periodontal ligament (PDL hTERT) cell line to model PFE and study molecular mechanisms in vitro. Functional assay revealed that while the mutated cell line displayed no major phenotypic changes, the PTH1R downstream signaling cascade, including cAMP synthesis and PKA activation, was disrupted. Techniques like FRET-based biosensors and VASP phosphorylation assays highlighted specific impairments in signaling pathways in cells with the PTH1R mutations

Chimpanzees steal less from their friends and expect them to do the same - Oded Ritov; Christoph J. Völter; Liran Samuni; Avi Benozio; Dacher Keltner; Jan M. Engelmann; Laura S. Lewis; Esther Herrmann (Evolution and Human Behavior, 2026)

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

Quantifying microplastics and their retention in greywater treatment systems of different scales - M. Sami; A. Hedström; H. Österlund; E. Kvarnström; P.D. Jenssen; M. Hartl; I. Herrmann (Journal of Hazardous Materials, 2026)

A rapid and robust translational model for testicular aging research - N. Schmid; Y. Stepanov; M. Offner; L. Scholz; C. Herrmann; S. Petkov; R. Behr; J. B. Stöckl; T. Fröhlich; A. Mayerhofer (Histochemistry and Cell Biology, 2026)
In humans, testicular peritubular cells (TPCs) form a small compartment surrounding the seminiferous tubules and, as shown previously, undergo age-related changes. How they may contribute to the age-associated decline of testicular functions is not well known. Likewise, the mechanisms of testicular aging in humans are not well examined. This is in part due to the lack of appropriate cellular models. We aimed to establish an aging model of TPCs, which is based on immortalized nonhuman primate (NHP) peritubular cells (iMKTPCs) from Callithrix jacchus . As shown previously by a comprehensive proteomic approach, they strongly resemble human TPCs but lack the human cell-intrinsic heterogeneity. Cellular senescence was robustly induced within 10 days upon exposure to 25 µg/mL bleomycin for 24 h. This resulted in increased β-galactosidase activity, enlarged cells, and elevated transcript levels of senescence-associated secretory phenotype (SASP) molecules ( IL1b , TNFa , CCL2 ). The ability to contract upon a stimulus was reduced, as shown in live cell imaging studies. Reduced proliferation among others was indicated by a decreased abundance of proliferating cell nuclear antigen (PCNA), evident in a proteomic analysis, which also revealed massive changes (341 significantly increased and 372 decreased proteins). Bioinformatics analysis indicated a marked reduction in several cell-motility–associated proteins, whereas proteins linked to extracellular exosomes, the cytoskeleton, and lysosomal pathways were increased in abundance. To conclude, bleomycin treatment causes a rapid and robust induction of cellular senescence in a translational testicular cell model of peritubular cells. This model will enable future studies aiming to explore mechanisms and consequences of testicular aging.

Long-term P management has limited impacts on soil microbial communities, with unique patterns driven by location, land use, and soil depth - Kirill Bogdanov; Parag Bhople; Giulia Bondi; Naoise Nunan; Lars Elsgaard; Anke M. Herrmann; Karl G. Richards; Mart Ros; David Wall; Fiona Brennan; Sergio E. Morales; Timothy J. Clough (Applied Soil Ecology, 2026)

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

NfL and GFAP quantification and associations with mental health in recreational cannabis users—Results from the Swiss study on recreational cannabis access via pharmacies - Maximilian Meyer; C. Felix Mosandl; Adrian Guessoum; Oliver Herrmann; Lavinia Baltes-Flückiger; Eva-Maria Pichler; Amar Zadic; Aleksandra Maleska Maceski; Juan Francisco Vilchez Gomez; Kenneth M. Dürsteler; Felix Müller; Undine E. Lang; et al. (Molecular Neurobiology, 2026)

Toluene photo-oxidation and secondary organic aerosol formation: EUROCHAMP-2020 multi-chamber experiments - Petro Uruci; Kalliopi Florou; Marco Paglione; Christos Kaltsonoudis; Bénédicte Picquet-Varrault; Jean-François Doussin; Mathieu Cazaunau; Ari Leskinen; Liqing Hao; Annele Virtanen; David M. Bell; Anke Mutzel; et al. (Journal of Atmospheric Chemistry, 2025)

Ecosystem Metabolic Rates Estimated from Diel Oxygen Measurements in Two Subtropical Estuaries - J. M. Arriola; R. G. Najjar; H. Briceño; C. Hu; M. Herrmann; M. W. Beck (Estuaries and Coasts, 2025)
Subtropical estuaries worldwide are facing increasing pressure from human population growth, development, and climate change. Carbon is a useful currency for understanding how estuaries respond to these pressures and yet relatively little is known about carbon cycling in subtropical estuaries. Here we compute gross primary production (GPP), ecosystem respiration (ER), and net ecosystem production (NEP) from the diurnal cycle in dissolved oxygen measured during 38 week-long individual deployments over three years in two estuaries in the southeastern United States, Biscayne Bay and Tampa Bay. On average for both estuaries, GPP and ER nearly balance, with NEP about an order of magnitude smaller. Even though production in Tampa Bay and Biscayne Bay is dominated by different primary producers and limiting nutrients, mean GPP was the same, about 190 mmol O 2 m –2 d –1 (570 g C m –2 y –1 ). Our GPP estimates for Biscayne Bay are more than an order of magnitude greater than the only other productivity estimates available for this system, which are planktonic net primary productivity measurements from the late 1970s. GPP was strongly correlated with water temperature in Biscayne Bay ( r = 0.60) but had the strongest correlation with salinity in Tampa Bay ( r = 0.39). These findings highlight the importance of more frequent production measurements in these complex estuaries, especially in the face of a changing climate.

Temporal Changes to Migratory Fuel Load in Migratory Birds Across Europe - Jennifer Anne Border; Robert A. Robinson; James W. Pearce‐Higgins; Chris M. Hewson; Christine Howard; Philip A. Stephens; Stephen G. Willis; Jan A. C. von Rönn; Pierre‐Yves Henry; Romain Lorrilliere; Lorenzo Serra; Simona Imperio; et al. (Global Change Biology, 2025)
Climate change is a major threat to biodiversity, and migratory animals are particularly vulnerable, due partly to their reliance upon good resource availability across a network of sites at specific times. Migrants perform vital ecosystem functions, transferring significant resources across large spatial scales, but the impacts of climate change on the ability of individuals to complete these journeys are poorly studied. Collecting the large‐scale and long‐term data on the condition of individuals during migration to address this is challenging, but in migratory birds, we have a model system for which a large network of ringers (banders) collect individual data on body size and mass, enabling variation in body condition to be tracked. We used long‐term ringing data on 33 Afro–Palearctic migratory bird species at 286 sites across Europe to demonstrate a large‐scale decrease in migratory fuel loads during autumn over the last 40 years, but not in spring. Declines were strongest across southern Europe and linked to rising temperatures. The timing of autumn fuelling has also shifted, occurring earlier at northern sites and later at southern sites. These relationships varied depending on diet and breeding cycle length. Obligate insectivores were more constrained by temperature in the timing and magnitude of fuelling than frugivores. Species with short breeding cycles departed later at southern sites in warmer years, likely reflecting an extended breeding season. Altogether, these latitudinally varying findings suggest a trade‐off between maximising productivity or maximising adult survival as climate drives changing constraints on breeding season length and resource availability. Similar climate‐induced trade‐offs may be happening in other migratory taxa with the potential to influence population trends.

Contrasting trends in wheat production exist across Australia in response to climate - Roger A. Lawes; Rose Roche; Rebecca O. Darbyshire; Aswin Singaram Natarajan; Chris M. Herrmann (European Journal of Agronomy, 2025)

P29-02 Comparative assessment of 24 poorly soluble, low toxicity dusts after short-term exposure - A. Herrmann; L. Puente; M. Dammann; L. Ma-Hock; H. Stratmann (Toxicology Letters, 2025)

Hard-seeded annual pasture legume phases are a profitable and low risk option in mixed farming regions with low to medium rainfall - Dean T. Thomas; Sadeeka L. Jayasinghe; Chris Herrmann; Robert J. Harrison; Bonnie M. Flohr; Roger A. Lawes (Agricultural Systems, 2025)

Salix species and varieties affect the molecular composition and diversity of soil organic matter - Louis J. P. Dufour; Johanna Wetterlind; Naoise Nunan; Katell Quenea; Andong Shi; Martin Weih; Anke M. Herrmann (Plant and Soil, 2025)
Background and aims Most studies of the relationships between the composition of soil organic matter and plant cover have been carried out at the plant genera level. However, they have largely overlooked the potential effects that plant varieties, belonging to the same genus, can have on soil organic matter. Methods We investigated whether plant varieties belonging to different Salix species ( S. dasyclados and S. viminalis) impacted the composition of organic matter using mid-infrared spectroscopy and pyrolysis GC/MS. Top-soils were taken from an 18 year-old long-term field trial where six Salix varieties were grown as short-rotation coppice under two fertilisation regimes. Results Significant differences in the molecular composition and diversity of the soil organic matter were observed in the fertilised plots. The effects were mostly visible at the species level, i.e. the organic matter in soil under S. dasyclados varieties had higher molecular diversity and lignin content than under S. viminalis , potentially due to differences in the amount and composition of their litter inputs. Smaller differences among varieties from the same species were also observed. No significant effects of Salix varieties were observed in the unfertilised plots. The relatively high degree of spatial variability of several soil properties found in these plots may have masked plant variety and/or species effects. Conclusion This study provides evidence that the identity of Salix species or varieties can affect the molecular composition and diversity of soil organic matter. The corresponding traits should be considered in breeding programmes to enhance soil organic C accumulation and persistence.

Rapid subsidence as a driver of phosphate deposition in the later Ordovician: Case study from the Alabama Appalachians - John T. Haynes; Rafael A. Villanueva; Richard M. Robinet; Stephen A. Leslie; Achim D. Herrmann (Sedimentary Geology, 2025)

River discharge - tide interactions and tide propagation in the mesotidal tropical estuary of the Van Uc river, Red River delta, Vietnam - J. Pénicaud; M. Herrmann; F. Toublanc; V.D. Vinh; S. Ouillon (Regional Studies in Marine Science, 2025)

Can pots be an alternative fishing gear to gillnets? A Mediterranean case study - M. Virgili; A. Petetta; B. Herrmann; K. Cerbule; S. Guicciardi; G. La Manna; L. Malvarosa; D. Li Veli; G. Barone; A. Lucchetti (Reviews in Fish Biology and Fisheries, 2024)
Small-scale coastal fisheries in the Mediterranean often employ gillnets, a widely used gear worldwide. The disadvantages of gillnets in this fishery include high bycatch levels of unwanted species and consequent discards. Moreover, spatial conflict with other gears and dolphin depredation often results in considerable economic loss. Alternative fishing methods are being tested. This study investigated whether, in small-scale fisheries in the Adriatic Sea, pots can ensure sustainable harvest of mantis shrimp ( Squilla mantis ), a major target demersal species in terms of landings, and possibly replace traditional gillnets. We adopted a multidisciplinary approach to investigate the catch efficiency, biological impact, and socio-economic effects of the two fishing methods. We found different species compositions in gillnet and pot catches. Gillnets yielded a greater number of discarded species of no commercial value, whereas pots caught a greater amount of mantis shrimp. Finally, a profit analysis indicated that pot fishery has the potential to increase profits for the commercial fishing industry. This study suggests that pots provide a more sustainable fishing method, both in terms of revenue and environmental impact.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

Evaluation of behavioral and neurochemical changes induced by carbofuran in zebrafish (Danio rerio) - Giovana R. Oliveira; Matheus Gallas-Lopes; Rafael Chitolina; Leonardo M. Bastos; Stefani M. Portela; Thailana Stahlhofer-Buss; Darlan Gusso; Rosane Gomez; Angela T.S. Wyse; Ana P. Herrmann; Angelo Piato (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Population balance modeling-assisted prediction of oxygen mass transfer coefficients with optical measurements - R. Herrmann-Heber; M. Oleshova; S.F. Reinecke; M. Meier; S. Taş; U. Hampel; A. Lerch (Journal of Water Process Engineering, 2024)

Study of thermal and photochemical aging of saturates, naphtenic-aromatics, resins, and asphaltene fractions of asphalt cement by FTIR and FT-ICR MS - Natã C.L. Madeira; Lindamara M. de Souza; Alan Reinke Pereira; Luiz S. Chinelatto; Margareth C.C. Cravo; Luis A. Herrmann do Nascimento; Valdemar Lacerda; Wanderson Romão (Fuel, 2024)

Beyond growth: The significance of non-growth anabolism for microbial carbon-use efficiency in the light of soil carbon stabilisation - Tobias Bölscher; Cordula Vogel; Folasade K. Olagoke; Katharina H.E. Meurer; Anke M. Herrmann; Tino Colombi; Melanie Brunn; Luiz A. Domeignoz-Horta (Soil Biology and Biochemistry, 2024)

Estimating energy costs of earthworm burrowing using calorimetry - Elsa M. Arrázola-Vásquez; Mats Larsbo; Yvan Capowiez; Astrid Taylor; Anke M. Herrmann; Thomas Keller (European Journal of Soil Biology, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Lithospheric- and crustal-scale controls on variations in foreland basin development in the Northern Alpine Foreland Basin - Lucas H.J. Eskens; Nevena Andrić-Tomašević; Peter M. Süss; Matthias Müller; Rolf Herrmann; Todd A. Ehlers (Tectonophysics, 2024)

Sneak Peek auf das CHE-Ranking der deutschen Biochemie-Studiengänge - Volker Haucke; Robert Tampé; Johannes M. Herrmann (BIOspektrum, 2024)

Local fractal dimension of collagen detects increased spatial complexity in fibrosis - Dylan T. Casey; Karolyn G. Lahue; Vitor Mori; Jacob Herrmann; Joseph K. Hall; Béla Suki; Yvonne M. W. Janssen-Heininger; Jason H. T. Bates (Histochemistry and Cell Biology, 2024)
Increase of collagen content and reorganization characterizes fibrosis but quantifying the latter remains challenging. Spatially complex structures are often analyzed via the fractal dimension; however, established methods for calculating this quantity either provide a single dimension for an entire object or a spatially distributed dimension that only considers binary images. These neglect valuable information related to collagen density in images of fibrotic tissue. We sought to develop a fractal analysis that can be applied to 3-dimensional (3D) images of fibrotic tissue. A fractal dimension map for each image was calculated by determining a single fractal dimension for a small area surrounding each image pixel, using fiber thickness as the third dimension. We found that this local fractal dimension increased with age and with progression of fibrosis regardless of collagen content. Our new method of distributed 3D fractal analysis can thus distinguish between changes in collagen content and organization induced by fibrosis.

Do ticks exhibit repeatable individual behaviors? - Hugh Lefcort; Matthew L. Hovancsek; Lindsey A. Bell; Erin K. Ellinwood; Elizabeth M. Freisinger; Katelin G. Herrmann; Jalisa R. Lau (Experimental and Applied Acarology, 2023)

Effect of manufacturing and frozen meat temperatures on structural and functional properties of hamburgers - Lisa M. Berger; Carsten Böckle; Monika Gibis; Kurt Herrmann; Nino Terjung; Jochen Weiss (Journal of Food Engineering, 2023)

Cadmium Reduction in Spring Wheat: Root Exudate Composition Affects Cd Partitioning Between Roots and Shoots - M. C. Affholder; A. A. Moazzami; M. Weih; H. Kirchmann; A. M. Herrmann (Journal of Soil Science and Plant Nutrition, 2023)
Cadmium (Cd) in cereals is one of the major sources of Cd intake by human diets, and solutions to reduce Cd concentrations in wheat still need to be developed. Plant breeding, by selecting low-Cd varieties, can be an important tool to reduce Cd in crops. Knowing the genotypic variation in Cd accumulation and furthering our understanding of the impact of root exudates composition on Cd accumulation in crops may provide valuable information for plant breeding. In this study, we selected nine spring wheat varieties and analysed the accumulation and distribution of Cd in shoots, roots, root surfaces and kernels in relation to their qualitative and quantitative composition of root exudates, determined by 1 H-NMR (Proton Nuclear Magnetic Resonance). Results showed that the Cd concentration in shoots at an early stage could be used as a predictor for Cd concentration in kernels. Total Cd uptake was not correlated to the mobility of Cd in the rhizosphere, but total Cd was negatively correlated to Cd adsorbed at the root surface. Furthermore, (i) exudation of organic acids (primarily succinate and acetate) increased Cd concentration in shoots, and (ii) exudation of nucleosides, DNA (deoxyribonucleic acid) degradation products, increased Cd adsorption at the root surface. Therefore, root exudates composition should be taken into account when selecting for low-Cd wheat traits.

Genotoxicity assessment: opportunities, challenges and perspectives for quantitative evaluations of dose–response data - Jakob Menz; Mario E. Götz; Ulrike Gündel; Rainer Gürtler; Kristin Herrmann; Stefanie Hessel-Pras; Carsten Kneuer; Franziska Kolrep; Dana Nitzsche; Ulrike Pabel; Benjamin Sachse; Sebastian Schmeisser; et al. (Archives of Toxicology, 2023)
Genotoxicity data are mainly interpreted in a qualitative way, which typically results in a binary classification of chemical entities. For more than a decade, there has been a discussion about the need for a paradigm shift in this regard. Here, we review current opportunities, challenges and perspectives for a more quantitative approach to genotoxicity assessment. Currently discussed opportunities mainly include the determination of a reference point (e.g., a benchmark dose) from genetic toxicity dose–response data, followed by calculation of a margin of exposure (MOE) or derivation of a health-based guidance value (HBGV). In addition to new opportunities, major challenges emerge with the quantitative interpretation of genotoxicity data. These are mainly rooted in the limited capability of standard in vivo genotoxicity testing methods to detect different types of genetic damage in multiple target tissues and the unknown quantitative relationships between measurable genotoxic effects and the probability of experiencing an adverse health outcome. In addition, with respect to DNA-reactive mutagens, the question arises whether the widely accepted assumption of a non-threshold dose–response relationship is at all compatible with the derivation of a HBGV. Therefore, at present, any quantitative genotoxicity assessment approach remains to be evaluated case-by-case. The quantitative interpretation of in vivo genotoxicity data for prioritization purposes, e.g., in connection with the MOE approach, could be seen as a promising opportunity for routine application. However, additional research is needed to assess whether it is possible to define a genotoxicity-derived MOE that can be considered indicative of a low level of concern. To further advance quantitative genotoxicity assessment, priority should be given to the development of new experimental methods to provide a deeper mechanistic understanding and a more comprehensive basis for the analysis of dose–response relationships.

Greywater treatment in a green wall using different filter materials and hydraulic loading rates - M. Sami; A. Hedström; E. Kvarnström; D.T. McCarthy; I. Herrmann (Journal of Environmental Management, 2023)

Factors affecting effluent quality in on-site wastewater treatment systems in the cold climates of Finland and Sweden - Juho Kinnunen; Pekka M. Rossi; Inga Herrmann; Anna-Kaisa Ronkanen; Elisangela Heiderscheidt (Journal of Cleaner Production, 2023)

Citizen science’s transformative impact on science, citizen empowerment and socio-political processes - Julia von Gönner; Thora M. Herrmann; Till Bruckermann; Michael Eichinger; Susanne Hecker; Friederike Klan; Julia Lorke; Anett Richter; Ulrike Sturm; Silke Voigt-Heucke; Wiebke Brink; Christin Liedtke; et al. (Socio-Ecological Practice Research, 2023)
Citizen science (CS) can foster transformative impact for science, citizen empowerment and socio-political processes. To unleash this impact, a clearer understanding of its current status and challenges for its development is needed. Using quantitative indicators developed in a collaborative stakeholder process, our study provides a comprehensive overview of the current status of CS in Germany, Austria and Switzerland. Our online survey with 340 responses focused on CS impact through (1) scientific practices, (2) participant learning and empowerment, and (3) socio-political processes. With regard to scientific impact, we found that data quality control is an established component of CS practice, while publication of CS data and results has not yet been achieved by all project coordinators (55%). Key benefits for citizen scientists were the experience of collective impact (“making a difference together with others”) as well as gaining new knowledge. For the citizen scientists’ learning outcomes, different forms of social learning, such as systematic feedback or personal mentoring, were essential. While the majority of respondents attributed an important value to CS for decision-making, only few were confident that CS data were indeed utilized as evidence by decision-makers. Based on these results, we recommend (1) that project coordinators and researchers strengthen scientific impact by fostering data management and publications, (2) that project coordinators and citizen scientists enhance participant impact by promoting social learning opportunities and (3) that project initiators and CS networks foster socio-political impact through early engagement with decision-makers and alignment with ongoing policy processes. In this way, CS can evolve its transformative impact.

Evaluating the Safety of Intra-Articular Mitotherapy in the Equine Model: A Potential Novel Treatment for Osteoarthritis - Jennifer M. Cassano; Krzysztof Marycz; Marta Horna; Marcos Perez Nogues; Jessica M. Morgan; Daniel B. Herrmann; Larry D. Galuppo; Natalia Vapniarsky (Journal of Equine Veterinary Science, 2023)

Simulation of steam/air leakage through small-scale cracked concrete specimen - L. Bahr; J. Sievers; M. Zemann; N. Herrmann (European Journal of Environmental and Civil Engineering, 2022)

Uremic mouse model to study vascular calcification and “inflamm-aging” - Markus Tölle; Cornelia Henkel; Jaqueline Herrmann; Christoph Daniel; Milen Babic; Mengdi Xia; Anna M. Schulz; Kerstin Amann; Markus van der Giet; Mirjam Schuchardt (Journal of Molecular Medicine, 2022)
Calcification and chronic inflammation of the vascular wall is a high-risk factor for cardiovascular mortality, especially in patients with chronic uremia. For the reduction or prevention of rapid disease progression, no specific treatment options are currently available. This study aimed to evaluate an adenine-based uremic mouse model for studying medial vessel calcification and senescence-associated secretory phenotype (SASP) changes of aortic tissue to unravel molecular pathogenesis and provide a model for therapy testing. The dietary adenine administration induced a stable and similar degree of chronic uremia in DBA2/N mice with an increase of uremia blood markers such as blood urea nitrogen, calcium, creatinine, alkaline phosphatase, and parathyroid hormone. Also, renal fibrosis and crystal deposits were detected upon adenine feeding. The uremic condition is related to a moderate to severe medial vessel calcification and subsequent elastin disorganization. In addition, expression of osteogenic markers as Bmp-2 and its transcription factor Sox-9 as well as p21 as senescence marker were increased in uremic mice compared to controls. Pro-inflammatory uremic proteins such as serum amyloid A, interleukin (Il)-1β, and Il-6 increased. This novel model of chronic uremia provides a simple method for investigation of signaling pathways in vascular inflammation and calcification and therefore offers an experimental basis for the development of potential therapeutic intervention studies. Graphical abstract

Expert’s view: eine neue Artikel-Reihe - Johannes M. Herrmann; Lutz Schmitt (BIOspektrum, 2022)

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Sea Ice Microbiota in the Antarctic Peninsula Modulates Cloud-Relevant Sea Spray Aerosol Production - Manuel Dall’Osto; Dolors Vaqué; Ana Sotomayor-Garcia; Miguel Cabrera-Brufau; Marta Estrada; Teresa Buchaca; Montserrat Soler; Sdena Nunes; Sebastian Zeppenfeld; Manuela van Pinxteren; Hartmut Herrmann; Heike Wex; et al. (Frontiers in Marine Science, 2022)
Sea spray aerosol (SSA) formation plays a major role in the climate system. The Antarctic Peninsula (AP) is affected by the greatest warming occurring in the Southern Ocean; changes in cryospheric and biological processes are being observed. Whilst there is some evidence that organic material produced by ice algae and/or phytoplankton in the high Arctic contributes to SSA, less is known about Antarctic Sea ice (sympagic) regions. To gain insight into the influence of Antarctic Sea ice biology and biogeochemistry on atmospheric aerosol, we report simultaneous water-air measurements made by means of in situ aerosol chamber experiments. For the first time, we present a methodology showing that the controlled plunging jet aerosol chamber settings do not cause major cell disruption on the studied sea ice ecosystems. Larger sea ice phytoplankton cells (>20 µm; mainly diatoms) tend to sediment at the bottom of the chamber (during the 24h experiment) and likely have a minor role on SSA production. When comparing four chamber experiments - we find that the two producing more SSA are the ones with highest abundance of nanophytoplankton cells (<20 µm; mainly nanoflagellates) as well as viruses. Our marine biogeochemical data show two broad groups of dissolved organic carbon: one rich in carbohydrates and proteic material and one rich in humic-like substances; the latter enhancing SSA production. This work provides unique insights into sea ice productivity that modulates SSA production, with potentially significant climate impacts. Further studies of these types are advised in order to see how microbiology impacts the biogeochemical cycling of elements and how aerosols are formed and processed in cold regions.

Evaluation of biotransformation capacity of transplastomic plants and hairy roots of Nicotiana tabacum expressing human cytochrome P450 2D6 - Y. V. Sheludko; I. M. Gerasymenko; F. J. Herrmann; H. Warzecha (Transgenic Research, 2022)
Cytochrome P450 monooxygenases (CYPs) are important tools for regio- and stereoselective oxidation of target molecules or engineering of metabolic pathways. Functional heterologous expression of eukaryotic CYPs is often problematic due to their dependency on the specific redox partner and the necessity of correct association with the membranes for displaying enzymatic activity. Plant hosts offer advantages of accessibility of reducing partners and a choice of membranes to insert heterologous CYPs. For the evaluation of plant systems for efficient CYP expression, we established transplastomic plants and hairy root cultures of Nicotiana tabacum carrying the gene encoding human CYP2D6 with broad substrate specificity. The levels of CYP2D6 transcript accumulation and enzymatic activity were estimated and compared with the data of CYP2D6 transient expression in N. benthamiana . The relative level of CYP2D6 transcripts in transplastomic plants was 2–3 orders of magnitude higher of that observed after constitutive or transient expression from the nucleus. CYP2D6 expressed in chloroplasts converted exogenous synthetic substrate loratadine without the need for co-expression of the cognate CYP reductase. The loratadine conversion rate in transplastomic plants was comparable to that in N. benthamiana plants transiently expressing a chloroplast targeted CYP2D6 from the nucleus, but was lower than the value reported for transiently expressed CYP2D6 with the native endoplasmic reticulum signal-anchor sequence. Hairy roots showed the lowest substrate conversion rate, but demonstrated the ability to release the product into the culture medium. The obtained results illustrate the potential of plant-based expression systems for exploiting the enzymatic activities of eukaryotic CYPs with broad substrate specificities.

Woolly beech aphid infestation reduces soil organic carbon availability and alters phyllosphere and rhizosphere bacterial microbiomes - Karin Potthast; Alexander Tischer; Martina Herrmann; Alexander Weinhold; Kirsten Küsel; Nicole M. van Dam; Beate Michalzik (Plant and Soil, 2022)
Purpose The woolly beech aphid thrives on European beech leaves, which has complex direct and indirect impacts on above- and belowground processes. A mechanistic understanding of insect-mediated changes in organic carbon (OC) availability for microbial life and its implications for element cycling is still lacking. This study aims at disentangling aphid-induced effects on phyllosphere and rhizosphere bacterial communities, as well as investigating feedbacks to OC transfer from the canopy to the mineral soil. Methods Following 2.5 months of infestation, we tracked the fate of OC ( 13 CO 2 pulse-labelling) in several compartments of beech sapling – soil mesocosms over 5 days. In ecosystem solutions, water extracts and soil/plant compartments we determined OC and N and solid δ 13 C. Bacterial community structure (16S rRNA gene targeted amplicon sequencing and quantitative PCR) and metabolite profiles (LC-qTOF-MS) were analysed. Results We found significantly higher aphid-mediated inputs of OC within throughfall. Honeydew-derived C on infested leaves was inconsequential for total phyllosphere bacterial abundances, but verifiably affected the community structure. In all soil compartments, cold-water extractable OC pools declined significantly by frequent inputs of readily available OC. This pattern might relate to reductions in rhizodepositions and altered microbial processing by accelerated soil C-mineralization. As a result, the abundance of metabolites changed significantly in different ecosystem solutions. Conclusions Our findings attest that insect infestations induce distinct direct and indirect effects on plant-insect-microbiome interactions leading to marked alterations in C dynamics. This integrated approach improves our understanding on microbial dynamics and biogeochemistry and evaluates the role of insects for ecosystem processes.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

The EU chemicals strategy for sustainability: in support of the BfR position - Frank A. Barile; Sir Colin Berry; Bas Blaauboer; Alan Boobis; Herrmann M. Bolt; Christopher Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Corrado L. Galli; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2021)
The EU chemicals strategy for sustainability (CSS) asserts that both human health and the environment are presently threatened and that further regulation is necessary. In a recent Guest Editorial, members of the German competent authority for risk assessment, the BfR, raised concerns about the scientific justification for this strategy. The complexity and interdependence of the networks of regulation of chemical substances have ensured that public health and wellbeing in the EU have continuously improved. A continuous process of improvement in consumer protection is clearly desirable but any initiative directed towards this objective must be based on scientific knowledge. It must not confound risk with other factors in determining policy. This conclusion is fully supported in the present Commentary including the request to improve both, data collection and the time-consuming and bureaucratic procedures that delay the publication of regulations.

Regional Gas Transport During Conventional and Oscillatory Ventilation Assessed by Xenon-Enhanced Computed Tomography - Jacob Herrmann; Sarah E. Gerard; Joseph M. Reinhardt; Eric A. Hoffman; David W. Kaczka (Annals of Biomedical Engineering, 2021)

Experimental Deformation of Opalinus Clay at Elevated Temperature and Pressure Conditions: Mechanical Properties and the Influence of Rock Fabric - Valerian Schuster; Erik Rybacki; Audrey Bonnelye; Johannes Herrmann; Anja M. Schleicher; Georg Dresen (Rock Mechanics and Rock Engineering, 2021)
The mechanical behavior of the sandy facies of Opalinus Clay (OPA) was investigated in 42 triaxial tests performed on dry samples at unconsolidated, undrained conditions at confining pressures ( p c ) of 50–100 MPa, temperatures ( T ) between 25 and 200 °C and strain rates ( $$\dot{ε }$$ ε ˙ ) of 1 × 10 –3 –5 × 10 –6 s −1 . Using a Paterson-type deformation apparatus, samples oriented at 0°, 45° and 90° to bedding were deformed up to about 15% axial strain. Additionally, the influence of water content, drainage condition and pre-consolidation was investigated at fixed p c – T conditions, using dry and re-saturated samples. Deformed samples display brittle to semi-brittle deformation behavior, characterized by cataclastic flow in quartz-rich sandy layers and granular flow in phyllosilicate-rich layers. Samples loaded parallel to bedding are less compliant compared to the other loading directions. With the exception of samples deformed 45° and 90° to bedding at p c = 100 MPa, strain is localized in discrete shear zones. Compressive strength ( σ max ) increases with increasing p c , resulting in an internal friction coefficient of ≈ 0.31 for samples deformed at 45° and 90° to bedding, and ≈ 0.44 for samples deformed parallel to bedding. In contrast, pre-consolidation, drainage condition, T and $$\dot{ε }$$ ε ˙ do not significantly affect deformation behavior of dried samples. However, σ max and Young’s modulus ( E ) decrease substantially with increasing water saturation. Compared to the clay-rich shaly facies of OPA, sandy facies specimens display higher strength σ max and Young’s modulus E at similar deformation conditions. Strength and Young’s modulus of samples deformed 90° and 45° to bedding are close to the iso-stress Reuss bound, suggesting a strong influence of weak clay-rich layers on the deformation behavior.

Hippocampal and Prefrontal Cortical Brain Tissue Levels of Irisin and GDF15 Receptor Subunits in Children - Travis C. Jackson; Kiersten Gorse; Jeremy R. Herrmann; Patrick M. Kochanek (Molecular Neurobiology, 2021)
Cold-stress hormones (CSHs) stimulate thermogenesis and have direct neuroprotective effects on the brain. The obligatory receptor components of two new CSHs (irisin and growth differentiation factor-15 [GDF15]) were recently discovered. Irisin binds integrin-αV/β5 heterodimers while GDF-15 binds to the orphan receptor glial cell-derived neurotrophic factor (GDNF) family receptor α-like (GFRAL). In addition, integrin-αV/β5 was just identified as the key receptor mediating Zika virus infection in the CNS. We measured integrin-αV, integrin-β5, and GFRAL protein levels across 78 high-quality human male/female brain tissues in infants, toddlers, preschoolers, adolescent, and adults—providing the most robust analysis to date on their levels in the human cortex and hippocampus. We report that integrin-αV was detected at all ages in the prefrontal cortex with levels greatest in adults. Integrin-αV was also detected in the hippocampus in all age groups. In contrast, integrin-β5 was detected in cortex and hippocampus largely restricted to infants. Co-expression of integrin-αV/β5 in the human infant hippocampus and cortex suggests the possibility that irisin has a more robust effect on the developing vs. the adult brain and may have implications for Zika virus infection in infants and young children.

Atmospheric CO2 availability induces varying responses in net photosynthesis, toxin production and N2 fixation rates in heterocystous filamentous Cyanobacteria (Nostoc and Nodularia) - Nicola Wannicke; Achim Herrmann; Michelle M. Gehringer (Aquatic Sciences, 2021)
Heterocystous Cyanobacteria of the genus Nodularia form major blooms in brackish waters, while terrestrial Nostoc species occur worldwide, often associated in biological soil crusts. Both genera, by virtue of their ability to fix N 2 and conduct oxygenic photosynthesis, contribute significantly to global primary productivity. Select Nostoc and Nodularia species produce the hepatotoxin nodularin and whether its production will change under climate change conditions needs to be assessed. In light of this, the effects of elevated atmospheric CO 2 availability on growth, carbon and N 2 fixation as well as nodularin production were investigated in toxin and non-toxin producing species of both genera. Results highlighted the following: Biomass and volume specific biological nitrogen fixation (BNF) rates were respectively almost six and 17 fold higher in the aquatic Nodularia species compared to the terrestrial Nostoc species tested, under elevated CO 2 conditions. There was a direct correlation between elevated CO 2 and decreased dry weight specific cellular nodularin content in a diazotrophically grown terrestrial Nostoc species, and the aquatic Nodularia species, regardless of nitrogen availability. Elevated atmospheric CO 2 levels were correlated to a reduction in biomass specific BNF rates in non-toxic Nodularia species. Nodularin producers exhibited stronger stimulation of net photosynthesis rates (NP) and growth (more positive Cohen’s d) and less stimulation of dark respiration and BNF per volume compared to non-nodularin producers under elevated CO 2 levels. This study is the first to provide information on NP and nodularin production under elevated atmospheric CO 2 levels for Nodularia and Nostoc species under nitrogen replete and diazotrophic conditions.

Die Biochemie-Studiengänge bekommen mehr Sichtbarkeit - Johannes M. Herrmann; Robert Tampé (BIOspektrum, 2021)

Composition and compound proportions affect the response to complex chemical signals in a spiny lizard - Cristina Romero-Diaz; Stephanie M. Campos; Morgan A. Herrmann; Helena A. Soini; Milos V. Novotny; Diana K. Hews; Emília P. Martins (Behavioral Ecology and Sociobiology, 2021)

A framework for modelling soil structure dynamics induced by biological activity - Katharina Meurer; Jennie Barron; Claire Chenu; Elsa Coucheney; Matthew Fielding; Paul Hallett; Anke M. Herrmann; Thomas Keller; John Koestel; Mats Larsbo; Elisabet Lewan; Dani Or; et al. (Global Change Biology, 2020)
Soil degradation is a worsening global phenomenon driven by socio‐economic pressures, poor land management practices and climate change. A deterioration of soil structure at timescales ranging from seconds to centuries is implicated in most forms of soil degradation including the depletion of nutrients and organic matter, erosion and compaction. New soil–crop models that could account for soil structure dynamics at decadal to centennial timescales would provide insights into the relative importance of the various underlying physical (e.g. tillage, traffic compaction, swell/shrink and freeze/thaw) and biological (e.g. plant root growth, soil microbial and faunal activity) mechanisms, their impacts on soil hydrological processes and plant growth, as well as the relevant timescales of soil degradation and recovery. However, the development of such a model remains a challenge due to the enormous complexity of the interactions in the soil–plant system. In this paper, we focus on the impacts of biological processes on soil structure dynamics, especially the growth of plant roots and the activity of soil fauna and microorganisms. We first define what we mean by soil structure and then review current understanding of how these biological agents impact soil structure. We then develop a new framework for modelling soil structure dynamics, which is designed to be compatible with soil–crop models that operate at the soil profile scale and for long temporal scales (i.e. decades, centuries). We illustrate the modelling concept with a case study on the role of root growth and earthworm bioturbation in restoring the structure of a severely compacted soil.

Toxicokinetics and toxicodynamics of the fentanyl homologs cyclopropanoyl-1-benzyl-4´-fluoro-4-anilinopiperidine and furanoyl-1-benzyl-4-anilinopiperidine - Tanja M. Gampfer; Lea Wagmann; Yu Mi Park; Annelies Cannaert; Jennifer Herrmann; Svenja Fischmann; Folker Westphal; Rolf Müller; Christophe P. Stove; Markus R. Meyer (Archives of Toxicology, 2020)
The two fentanyl homologs cyclopropanoyl-1-benzyl-4´-fluoro-4-anilinopiperidine (4F-Cy-BAP) and furanoyl-1-benzyl-4-anilinopiperidine (Fu-BAP) have recently been seized as new psychoactive substances (NPS) on the drugs of abuse market. As their toxicokinetic and toxicodynamic characteristics are completely unknown, this study focused on elucidating their in vitro metabolic stability in pooled human liver S9 fraction (pHLS9), their qualitative in vitro (pHLS9), and in vivo (zebrafish larvae) metabolism, and their in vitro isozyme mapping using recombinant expressed isoenzymes. Their maximum-tolerated concentration (MTC) in zebrafish larvae was studied from 0.01 to 100 µM. Their µ-opioid receptor (MOR) activity was analyzed in engineered human embryonic kidney (HEK) 293 T cells. In total, seven phase I and one phase II metabolites of 4F-Cy-BAP and 15 phase I and four phase II metabolites of Fu-BAP were tentatively identified by means of liquid chromatography high-resolution tandem mass spectrometry, with the majority detected in zebrafish larvae. N -Dealkylation, N -deacylation, hydroxylation, and N -oxidation were the most abundant metabolic reactions and the corresponding metabolites are expected to be promising analytical targets for toxicological analysis. Isozyme mapping revealed the main involvement of CYP3A4 in the phase I metabolism of 4F-Cy-BAP and in terms of Fu-BAP additionally CYP2D6. Therefore, drug-drug interactions by CYP3A4 inhibition may cause elevated drug levels and unwanted adverse effects. MTC experiments revealed malformations and changes in the behavior of larvae after exposure to 100 µM Fu-BAP. Both substances were only able to produce a weak activation of MOR and although toxic effects based on MOR activation seem unlikely, activity at other receptors cannot be excluded.

Differential Bioaccumulation of Mercury and Selenium in Stomach Contents and Tissues of Three Colorado, USA, Cutthroat Trout Populations - Scott J. Herrmann; Del Wayne R. Nimmo; James S. Carsella; Igor V. Melnykov; Christopher M. Kennedy; Kevin B. Rogers; Lynn M. Herrmann-Hoesing (Bulletin of Environmental Contamination and Toxicology, 2020)

A one year study of functionalised medium-chain carboxylic acids in atmospheric particles at a rural site in Germany revealing seasonal trends and possible sources - M. Teich; D. van Pinxteren; H. Herrmann (Journal of Atmospheric Chemistry, 2019)

N-Acetylcysteine Reverses Anxiety and Oxidative Damage Induced by Unpredictable Chronic Stress in Zebrafish - Ricieri Mocelin; Matheus Marcon; Simone D’ambros; Juliane Mattos; Adrieli Sachett; Anna M. Siebel; Ana P. Herrmann; Angelo Piato (Molecular Neurobiology, 2019)

Overexpression of branched-chain amino acid aminotransferases rescues the growth defects of cells lacking the Barth syndrome-related gene TAZ1 - Diana Antunes; Arpita Chowdhury; Abhishek Aich; Sreedivya Saladi; Nofar Harpaz; Mark Stahl; Maya Schuldiner; Johannes M. Herrmann; Peter Rehling; Doron Rapaport (Journal of Molecular Medicine, 2019)

Reduced spontaneous low frequency oscillations as measured with functional near-infrared spectroscopy in mild cognitive impairment - Julia B. M. Zeller; Andrea Katzorke; Laura D. Müller; Judith Breunig; Florian B. Haeussinger; Jürgen Deckert; Bodo Warrings; Martin Lauer; Thomas Polak; Martin J. Herrmann (Brain Imaging and Behavior, 2019)

Connectivity increases trophic subsidies in fragmented landscapes - Christine L. Hawn; John D. Herrmann; Sean R. Griffin; Nick M. Haddad (Ecology Letters, 2018)
Landscape corridors mitigate the negative effects of habitat fragmentation by increasing dispersal. Corridors also increase biodiversity in connected habitat fragments, suggestive of metacommunity dynamics. What is unknown in this case is the mechanisms through which metacommunity dynamics act. Working in a large‐scale fragmentation experiment, we tested the effect of corridors on the movement of prey species and subsequent effects on predator nutrition (which we call trophic subsidies). We enriched plants of central patches with 15 N, then measured δ 15 N in green lynx spiders, the most abundant insect predator, in patches that were either connected to or isolated from the enriched patch. We found that corridors increased prey movement, as they increased spider δ 15 N by 40% in connected patches. Corridors also improved spider body condition, increasing nitrogen relative to carbon. We suggest a novel mechanism, trophic subsidies, through which corridors may increase the stability or size of populations in connected landscapes.

Protective potential of dimethyl fumarate in a mouse model of thalamocortical demyelination - Manuela Cerina; Venu Narayanan; Anna Delank; Patrick Meuth; Stephanie Graebenitz; Kerstin Göbel; Alexander M. Herrmann; Stefanie Albrecht; Thiemo Daldrup; Thomas Seidenbecher; Ali Gorji; Tanja Kuhlmann; et al. (Brain Structure and Function, 2018)

ScalA-FS: expert-based ex-ante assessments of local requirements and success potential of upgrading strategies for improving food security in rural Tanzania - Götz Uckert; Frieder Graef; Anja Faße; Ludger Herrmann; Harry Hoffmann; Frederick C. Kahimba; Luitfred Kissoly; Hannes J. König; Christine Lambert; Henry Mahoo; Bashir Makoko; Leon Mrosso; et al. (Food Security, 2018)

ForC: a global database of forest carbon stocks and fluxes - Kristina J. Anderson‐Teixeira; Maria M. H. Wang; Jennifer C. McGarvey; Valentine Herrmann; Alan J. Tepley; Ben Bond‐Lamberty; David S. LeBauer (Ecology, 2018)
Forests play an influential role in the global carbon (C) cycle, storing roughly half of terrestrial C and annually exchanging with the atmosphere more than five times the carbon dioxide ( CO 2 ) emitted by anthropogenic activities. Yet, scaling up from field‐based measurements of forest C stocks and fluxes to understand global scale C cycling and its climate sensitivity remains an important challenge. Tens of thousands of forest C measurements have been made, but these data have yet to be integrated into a single database that makes them accessible for integrated analyses. Here we present an open‐access global Forest Carbon database (ForC) containing previously published records of field‐based measurements of ecosystem‐level C stocks and annual fluxes, along with disturbance history and methodological information. ForC expands upon the previously published tropical portion of this database, TropForC ( https://doi.org/10.5061/dryad.t516f ), now including 17,367 records (previously 3,568) representing 2,731 plots (previously 845) in 826 geographically distinct areas. The database covers all forested biogeographic and climate zones, represents forest stands of all ages, and currently includes data collected between 1934 and 2015. We expect that ForC will prove useful for macroecological analyses of forest C cycling, for evaluation of model predictions or remote sensing products, for quantifying the contribution of forests to the global C cycle, and for supporting international efforts to inventory forest carbon and greenhouse gas exchange. A dynamic version of ForC is maintained at on GitHub ( https://GitHub.com/forc-db ) , and we encourage the research community to collaborate in updating, correcting, expanding, and utilizing this database. ForC is an open access database, and we encourage use of the data for scientific research and education purposes. Data may not be used for commercial purposes without written permission of the database PI . Any publications using ForC data should cite this publication and Anderson‐Teixeira et al. (2016a) (see Metadata S1 ). No other copyright or cost restrictions are associated with the use of this data set.

Effect of fish length and nutritional condition on the fecundity of distressed Atlantic cod Gadus morhua from the Baltic Sea - M. Mion; A. Thorsen; F. Vitale; J. Dierking; J. P. Herrmann; B. Huwer; B. von Dewitz; M. Casini (Journal of Fish Biology, 2018)
The disappearance of larger individuals and the decrease in individual body condition suffered by Atlantic cod Gadus morhua in the eastern Baltic during the past two decades can be expected to affect the stock reproductive output. To investigate this, female G. morhua were collected during the spawning and pre‐spawning period in 2015−2016. The current individual potential fecundity ( F P ) of eastern Baltic G. morhua was estimated and analysed in relation to total length ( L T ) and indices of nutritional status such as body condition ( K ) and hepato‐somatic index ( I H ) using generalized linear models. In addition, the current prevalence of atresia and its potential relation to K were investigated. Moreover, a calibration curve to estimate F P from oocyte diameter, based on the autodiametric oocyte counting method, was established for the first time for eastern Baltic G. morhua and can be used for future fecundity studies on this stock. The results showed that F P was mainly positively related to fish length, but K and I H also contributed significantly to the variation in F P . The model predicted that fish with K = 1·2 have a F P 51% higher than fish of the same L T with K = 0·8. The prevalence of fecundity regulation by atresia was 5·8%, but it was found only in fish in the pre‐spawning maturity stage and with low K . Temporal changes in biological features such as the length composition and individual body condition of eastern Baltic G. morhua , should be accounted for when estimating stock reproductive potential.

Measurements of PM10 ions and trace gases with the online system MARGA at the research station Melpitz in Germany – A five-year study - B. Stieger; G. Spindler; B. Fahlbusch; K. Müller; A. Grüner; L. Poulain; L. Thöni; E. Seitler; M. Wallasch; H. Herrmann (Journal of Atmospheric Chemistry, 2018)

Changes in motor performance and mental workload during practice of reaching movements: a team dynamics perspective - Isabelle M. Shuggi; Patricia A. Shewokis; Jeffrey W. Herrmann; Rodolphe J. Gentili (Experimental Brain Research, 2018)

Methyleugenol DNA adducts in human liver are associated with SULT1A1 copy number variations and expression levels - Roman Tremmel; Kristin Herrmann; Wolfram Engst; Walter Meinl; Kathrin Klein; Hansruedi Glatt; Ulrich M. Zanger (Archives of Toxicology, 2017)

Prolonged suppressive antibiotic therapy for prosthetic joint infection in the elderly: a national multicentre cohort study - V. Prendki; T. Ferry; P. Sergent; E. Oziol; E. Forestier; T. Fraisse; S. Tounes; S. Ansart; J. Gaillat; S. Bayle; O. Ruyer; F. Borlot; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

An interstate highway affects gene flow in a top reptilian predator (Crotalus atrox) of the Sonoran Desert - Hans-Werner Herrmann; Krystyn M. Pozarowski; Alexander Ochoa; Gordon W. Schuett (Conservation Genetics, 2017)

The Ocean's Vital Skin: Toward an Integrated Understanding of the Sea Surface Microlayer - Anja Engel; Hermann W. Bange; Michael Cunliffe; Susannah M. Burrows; Gernot Friedrichs; Luisa Galgani; Hartmut Herrmann; Norbert Hertkorn; Martin Johnson; Peter S. Liss; Patricia K. Quinn; Markus Schartau; et al. (Frontiers in Marine Science, 2017)

Efficacy of cold fogging and oral herbal extracts on air quality and immune response of broilers - Awad A. Shehata; Klaus Herrmann; Thomas Pfalz; Hafez M. Hafez; Wieland Schrödl; Monika Krüger (Aerobiologia, 2017)

Cocaine administration dose-dependently increases sexual desire and decreases condom use likelihood: The role of delay and probability discounting in connecting cocaine with HIV - Matthew W. Johnson; Evan S. Herrmann; Mary M. Sweeney; Robert S. LeComte; Patrick S. Johnson (Psychopharmacology, 2017)

The role of digital data entry in participatory environmental monitoring - Jeremy R. Brammer; Nicolas D. Brunet; A. Cole Burton; Alain Cuerrier; Finn Danielsen; Kanwaljeet Dewan; Thora Martina Herrmann; Micha V. Jackson; Rod Kennett; Guillaume Larocque; Monica Mulrennan; Arun Kumar Pratihast; et al. (Conservation Biology, 2016)
Many argue that monitoring conducted exclusively by scientists is insufficient to address ongoing environmental challenges. One solution entails the use of mobile digital devices in participatory monitoring (PM) programs. But how digital data entry affects programs with varying levels of stakeholder participation, from nonscientists collecting field data to nonscientists administering every step of a monitoring program, remains unclear. We reviewed the successes, in terms of management interventions and sustainability, of 107 monitoring programs described in the literature (hereafter programs) and compared these with case studies from our PM experiences in Australia, Canada, Ethiopia, Ghana, Greenland, and Vietnam (hereafter cases). Our literature review showed that participatory programs were less likely to use digital devices, and 2 of our 3 more participatory cases were also slow to adopt digital data entry. Programs that were participatory and used digital devices were more likely to report management actions, which was consistent with cases in Ethiopia, Greenland, and Australia. Programs engaging volunteers were more frequently reported as ongoing, but those involving digital data entry were less often sustained when data collectors were volunteers. For the Vietnamese and Canadian cases, sustainability was undermined by a mismatch in stakeholder objectives. In the Ghanaian case, complex field protocols diminished monitoring sustainability. Innovative technologies attract interest, but the foundation of effective participatory adaptive monitoring depends more on collaboratively defined questions, objectives, conceptual models, and monitoring approaches. When this foundation is built through effective partnerships, digital data entry can enable the collection of more data of higher quality. Without this foundation, or when implemented ineffectively or unnecessarily, digital data entry can be an additional expense that distracts from core monitoring objectives and undermines project sustainability. The appropriate role of digital data entry in PM likely depends more on the context in which it is used and less on the technology itself.

Prevention of unpredictable chronic stress-related phenomena in zebrafish exposed to bromazepam, fluoxetine and nortriptyline - Matheus Marcon; Ana P. Herrmann; Ricieri Mocelin; Cassiano L. Rambo; Gessi Koakoski; Murilo S. Abreu; Greicy M. M. Conterato; Luiza W. Kist; Maurício R. Bogo; Leila Zanatta; Leonardo J. G. Barcellos; Angelo L. Piato (Psychopharmacology, 2016)

HC-Induced Deactivation in CO Conversion at Diesel Oxidation Catalysts - M. Herrmann; S. Malmberg; A. Drochner; H. Vogel; R. Hayes; M. Votsmeier (Emission Control Science and Technology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Differences in substrate use efficiency: impacts of microbial community composition, land use management, and substrate complexity - Tobias Bölscher; Lars Wadsö; Gunnar Börjesson; Anke M. Herrmann (Biology and Fertility of Soils, 2016)

Connectivity from a different perspective: comparing seed dispersal kernels in connected vs. unfragmented landscapes - John D. Herrmann; Tomás A. Carlo; Lars A. Brudvig; Ellen I. Damschen; Nick M. Haddad; Douglas J. Levey; John L. Orrock; Joshua J. Tewksbury (Ecology, 2016)
Habitat fragmentation can create significant impediments to dispersal. A technique to increase dispersal between otherwise isolated fragments is the use of corridors. Although previous studies have compared dispersal between connected fragments to dispersal between unconnected fragments, it remains unknown how dispersal between fragments connected by a corridor compares to dispersal in unfragmented landscapes. To assess the extent to which corridors can restore dispersal in fragmented landscapes to levels observed in unfragmented landscapes, we employed a stable‐isotope marking technique to track seeds within four unfragmented landscapes and eight experimental landscapes with fragments connected by corridors. We studied two wind‐ and two bird‐dispersed plant species, because previous community‐based research showed that dispersal mode explains how connectivity effects vary among species. We constructed dispersal kernels for these species in unfragmented landscapes and connected fragments by marking seeds in the center of each landscape with 15 N and then recovering marked seeds in seed traps at distances up to 200 m. For the two wind‐dispersed plants, seed dispersal kernels were similar in unfragmented landscapes and connected fragments. In contrast, dispersal kernels of bird‐dispersed seeds were both affected by fragmentation and differed in the direction of the impact: Morella cerifera experienced more and Rhus copallina experienced less long‐distance dispersal in unfragmented than in connected landscapes. These results show that corridors can facilitate dispersal probabilities comparable to those observed in unfragmented landscapes. Although dispersal mode may provide useful broad predictions, we acknowledge that similar species may respond uniquely due to factors such as seasonality and disperser behavior. Our results further indicate that prior work has likely underestimated dispersal distances of wind‐dispersed plants and that factors altering long‐distance dispersal may have a greater impact on the spread of species than previously thought.

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

Accumulation of Traffic-Related Trace Metals in Urban Winter-Long Roadside Snowbanks - S. Moghadas; K. H. Paus; T. M. Muthanna; I. Herrmann; J. Marsalek; M. Viklander (Water, Air, & Soil Pollution, 2015)

Photocatalytic abatement results from a model street canyon - M. Gallus; R. Ciuraru; F. Mothes; V. Akylas; F. Barmpas; A. Beeldens; F. Bernard; E. Boonen; A. Boréave; M. Cazaunau; N. Charbonnel; H. Chen; et al. (Environmental Science and Pollution Research, 2015)

Analysing the effect of soil organic matter on bacterial communities using T-RFLP fingerprinting: different methods, different stories? - A. Blaud; F. Diouf; A. M. Herrmann; T. Z. Lerch (Biology and Fertility of Soils, 2015)

Mutations of the SLIT2–ROBO2 pathway genes SLIT2 and SRGAP1 confer risk for congenital anomalies of the kidney and urinary tract - Daw-Yang Hwang; Stefan Kohl; Xueping Fan; Asaf Vivante; Stefanie Chan; Gabriel C. Dworschak; Julian Schulz; Albertien M. van Eerde; Alina C. Hilger; Heon Yung Gee; Tracie Pennimpede; Bernhard G. Herrmann; et al. (Human Genetics, 2015)

Relationships between feeding, growth and swimming activity of European sprat (Sprattus sprattus L.) post-larvae in the laboratory - Myron A. Peck; Bianca Ewest; Jens-Peter Herrmann; Fahad A. Al-Misned; M. Golam Mortuza; Sven Stäcker; Axel Temming (Environmental Biology of Fishes, 2015)

Chemical properties of HULIS from three different environments - T. B. Kristensen; L. Du; Q. T. Nguyen; J. K. Nøjgaard; C. Bender Koch; O. Faurskov Nielsen; A. G. Hallar; D. H. Lowenthal; B. Nekat; D. van Pinxteren; H. Herrmann; M. Glasius; et al. (Journal of Atmospheric Chemistry, 2015)

Vγ9 and Vδ2 T cell antigen receptor genes and butyrophilin 3 (BTN3) emerged with placental mammals and are concomitantly preserved in selected species like alpaca (Vicugna pacos) - Mohindar M. Karunakaran; Thomas W. Göbel; Lisa Starick; Lutz Walter; Thomas Herrmann (Immunogenetics, 2014)

Reference ranges and cutoff levels of pneumococcal antibody global serum assays (IgG and IgG2) and specific antibodies in healthy children and adults - M. A. Rose; J. Buess; Y. Ventur; S. Zielen; E. Herrmann; J. Schulze; R. Schubert (Medical Microbiology and Immunology, 2013)

Der mitochondriale Intermembranraum ist voller Überraschungen - Johannes M. Herrmann (BIOspektrum, 2013)

Particle Size Reduction during Harvesting of Crop Feedstock for Biogas Production I: Effects on Ensiling Process and Methane Yields - C. Herrmann; M. Heiermann; C. Idler; A. Prochnow (BioEnergy Research, 2012)

Particle Size Reduction During Harvesting of Crop Feedstock for Biogas Production II: Effects on Energy Balance, Greenhouse Gas Emissions and Profitability - C. Herrmann; A. Prochnow; M. Heiermann; C. Idler (BioEnergy Research, 2012)

H-D exchange on graphite–potassium intercalation compounds - Siegbert Rummel; Michael Herrmann; Manfred Wahren; Safar M. Yunusov; Margarita A. Ilatovskaya; Yuri B. Isaev; N. D. Lapkina; Yuri N. Novikov; Vladimir B. Shur (Isotopes in Environmental and Health Studies, 2012)

Effects of habitat isolation and predation pressure on an arboreal food-web - J. Herrmann; U. Kormann; C. Schüepp; Y. Stocker; F. Herzog; M. Entling (Community Ecology, 2012)

Modified light use efficiency model for assessment of carbon sequestration in grasslands of Kazakhstan: combining ground biomass data and remote-sensing - Pavel A. Propastin; Martin W. Kappas; Stefanie M. Herrmann; Compton J. Tucker (International Journal of Remote Sensing, 2012)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

An atmosphere–ocean regional climate model for the Mediterranean area: assessment of a present climate simulation - Vincenzo Artale; Sandro Calmanti; Adriana Carillo; Alessandro Dell’Aquila; Marine Herrmann; Giovanna Pisacane; Paolo M. Ruti; Gianmaria Sannino; Maria Vittoria Struglia; Filippo Giorgi; Xunqiang Bi; Jeremy S. Pal; et al. (Climate Dynamics, 2010)

Effect of temperature on the gastric evacuation in sprat Sprattus sprattus - M. Bernreuther; A. Temming; J.‐P. Herrmann (Journal of Fish Biology, 2009)
Gastric evacuation of groups of juvenile (mean 63 mm total length, L T , 0·283 g dry mass, M D ) sprat Sprattus sprattus feeding on brine shrimp Artemia sp. nauplii was studied at six temperatures (7·5, 10, 13, 16, 19·5 and 21·5° C) in the laboratory. Gastric evacuation was best described with a general model: , with S t = stomach content at time t , S 0 = stomach content at time 0, t = time , R , B = constants. The shape parameter was estimated as B = 0·668. For comparison with other studies, an exponential model was fitted also to the data. The evacuation constant ( R ) of the general gastric evacuation model increased exponentially with temperature between 7·5 and 16° C. The slope of the increase was reduced between 16 and 19·5° C and a slight decrease was observed between 19 and 21·5° C. Additionally, the effect of mean M D (range 0·286 – 1·025 g) was examined. A simple power function ( ) described the influence of predator mass on exponential evacuation constant with C = 0·503. The results of this investigation were integrated into a consumption model for the calculation of daily rations of S. sprattus : , with T = ambient temperature (°C) and of field stomach contents (g dry) individually raised to the power of 0·668.

Ovine progressive pneumonia provirus levels associate with breed and Ovar-DRB1 - Lynn M. Herrmann-Hoesing; Stephen N. White; Michelle R. Mousel; Gregory S. Lewis; Donald P. Knowles (Immunogenetics, 2008)

Complete nucleotide sequence of the Oenothera elata plastid chromosome, representing plastome I of the five distinguishable Euoenothera plastomes - H. Hupfer; M. Swiatek; S. Hornung; R. G. Herrmann; R. M. Maier; W.-L. Chiu; B. Sears (Molecular Genetics and Genomics, 2008)

Secondary structure and distribution of fusogenic LV-peptides in lipid membranes - J. Ollesch; B. C. Poschner; J. Nikolaus; M. W. Hofmann; A. Herrmann; K. Gerwert; D. Langosch (European Biophysics Journal, 2008)

Genomic analysis of Ovis aries (Ovar) MHC class IIa loci - Lynn M. Herrmann-Hoesing; Stephen N. White; Lowell S. Kappmeyer; David R. Herndon; Donald P. Knowles (Immunogenetics, 2008)

Endoparasite spectrum of wild cats (Felis silvestris Schreber, 1777) and domestic cats (Felis catus L.) from the Eifel, Pfalz region and Saarland, Germany - O. Krone; O. Guminsky; H. Meinig; M. Herrmann; M. Trinzen; G. Wibbelt (European Journal of Wildlife Research, 2008)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)

Isolation of fatty acids and aromatics from cell suspension cultures of Lavandula angustifolia - GülaÇti TopÇu; Gabriele Herrmann; Ufuk Kolak; C. Gören; Andrea Porzel; Toni M. Kutchan (Natural Product Research, 2007)

Abschätzung des akuten Risikos durch Pflanzenschutzmittel-Rückstände in Lebensmitteln auf der Basis von Daten aus amtlicher Überwachung und Eigenkontrollen - U. Banasiak; M. Herrmann; K. Hohgardt; B. Michalski; C. Sieke (Journal of Consumer Protection and Food Safety, 2007)

Inheritance and mapping of a powdery mildew resistance gene introgressed from Avena macrostachya in cultivated oat - J. Yu; M. Herrmann (Theoretical and Applied Genetics, 2006)

Lychee tree parameters for water balance modeling - K. Spohrer; C. Jantschke; L. Herrmann; M. Engelhardt; S. Pinmanee; K. Stahr (Plant and Soil, 2006)

Identification and phylogenetic analysis of 15 MHC class II DRB1 β1 expressed alleles in a ewe–lamb flock - Lynn M. Herrmann; Wendy C. Brown; Greg S. Lewis; Donald P. Knowles (Immunogenetics, 2005)

Induction of apoptosis by spermine-metabolites in primary human blood cells and various tumor cell lines - M. Schiller; N. Blank; P. Heyder; M. Herrmann; U. S. Gaipl; J. R. Kalden; H. M. Lorenz (Apoptosis, 2005)

From Single Genes to Co-Expression Networks: Extracting Knowledge from Barley Functional Genomics - P. Faccioli; P. Provero; C. Herrmann; A. M. Stanca; C. Morcia; V. Terzi (Plant Molecular Biology, 2005)

Frequency of Norovirus in stool samples from patients with gastrointestinal symptoms in Switzerland - R. Fretz; L. Herrmann; A. Christen; P. Svoboda; O. Dubuis; E. H. Viollier; M. Tanner; A. Baumgartner (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Temporal niches of shredders in lake littorals with possible implications on ecosystem functioning - Ulf Bjelke; Irene M. Bohman; Jan Herrmann (Aquatic Ecology, 2005)

Ontogenic changes in the allometric scaling of the mass and length relationship in Sprattus sprattus - M. A. Peck; C. Clemmesen; J.‐P. Herrmann (Journal of Fish Biology, 2005)
An analysis of mass ( M ) and standard length ( L S ) data for larval, juvenile and adult sprat ( Sprattus sprattus ; Clupeidae) revealed marked changes in the allometric scaling factor ( b in ). For sprat L S , b was 5·0, whereas in larger juveniles and adults, b was c. 3·4 indicating a relatively protracted metamorphic period for this species.

Comparative analysis of adenoviral transgene delivery via tail or portal vein into rat liver - J. Herrmann; B. Abriss; E. van de Leur; S. Weiskirchen; A. M. Gressner; R. Weiskirchen (Archives of Virology, 2004)

Genetic distinction of wildcat ( Felis silvestris ) populations in Europe, and hybridization with domestic cats in Hungary - M. Pierpaoli; Z. S. Birò; M. Herrmann; K. Hupe; M. Fernandes; B. Ragni; L. Szemethy; E. Randi (Molecular Ecology, 2003)
The genetic integrity and evolutionary persistence of declining wildcat populations are threatened by crossbreeding with widespread free‐living domestic cats. Here we use allelic variation at 12 microsatellite loci to describe genetic variation in 336 cats sampled from nine European countries. Cats were identified as European wildcats ( Felis silvestris silvestris ), Sardinian wildcats ( F. s. libyca ) and domestic cats ( F. s. catus ), according to phenotypic traits, geographical locations and independently of any genetic information. Genetic variability was significantly partitioned among taxonomic groups ( F ST = 0.11; R ST = 0.41; P F ST = 0.07; R ST = 0.06; P

Early maps as stepping stones for the reconstruction of historic ecological conditions and biota - Bernd Herrmann; Antje Jakupi; Peter-M. Steinsiek (The Science of Nature, 2003)

The dynamics of sleep-like behaviour in honey bees - S. Sauer; M. Kinkelin; E. Herrmann; W. Kaiser (Journal of Comparative Physiology A, 2003)

Effects of selective inactivation of individual genes for low-molecular-mass subunits on the assembly of photosystem II, as revealed by chloroplast transformation: the psbEFLJ operon in Nicotiana tabacum - M. Swiatek; R. E. Regel; J. Meurer; G. Wanner; H. B. Pakrasi; I. Ohad; R. G. Herrmann (Molecular Genetics and Genomics, 2003)

Photocatalytic degradation of the herbicide cinosulfuron in aqueous TiO 2 suspension - E. Vulliet; C. Emmelin; J.-M. Chovelon; C. Guillard; J.-M. Herrmann (Environmental Chemistry Letters, 2003)

Treatment of Severe Candida Infections in High-Risk Patients in Germany: Consensus Formed by a Panel of Interdisciplinary Investigators - Büchner T.; Fegeler W.; Bernhardt H.; Brockmeyer N.; Duswald K.-H.; Herrmann M.; Heuser D.; Jehn U.; Just-Nübling G.; Karthaus M.; Maschmeyer G.; Müller F.-M.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Webmapping — Thesen, Beispiele und Tendenzen - Christian M. Herrmann (KN - Journal of Cartography and Geographic Information, 2001)

The plastid chromosome of spinach (Spinacia oleracea): complete nucleotide sequence and gene organization - Christian Schmitz-Linneweber; Rainer M. Maier; Jean-Pierre Alcaraz; Annick Cottet; Reinhold G. Herrmann; Regis Mache (Plant Molecular Biology, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Role of apoptosis in autoimmunity - H-M. Lorenz; M. Herrmann; T. Winkler; U. Gaipl; J. R. Kalden (Apoptosis, 2000)

A polymorphism of the rat T-cell receptor β-chain variable gene 13 ( BV13S1 ) correlates with the frequency of BV13S1-positive CD4 cells - M. Stienekemeier; K. Hofmann; R. Gold; T. Herrmann (Immunogenetics, 2000)

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Physical mapping and molecular-cytogenetic analysis of substitutions and translocations involving chromosome 1D in synthetic hexaploid triticale - U. Hohmann; J. Zoller; R. G. Herrmann; M. E. Kazman (Theoretical and Applied Genetics, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Effect of dimethicone (polysilane gel) on the stereoselective pharmacokinetics of ketoprofen - N. Presle; F. Lapicque; P. Gillet; M.-A. Herrmann; B. Bannwarth; P. Netter (European Journal of Clinical Pharmacology, 1998)

Tissue culture of wild-type, interspecific genome/plastome hybrids and plastome mutants of evening primrose ( Oenothera) : controlled morphogenesis and transformation - A. Mehra-Palta; H.-U. Koop; S. Goes; E.-M. Troidl; G. Nagy; S. Tyagi; W. Kofer; R. G. Herrmann (Plant Cell Reports, 1998)

UV-B Irradiated Cell Lines Execute Programmed Cell Death in Various Forms - M. Hagenhofer; H. Germaier; C. Hohenadl; P. Rohwer; J. R. Kalden; M. Herrmann (Apoptosis, 1998)

Time behavior of topological ordering in self-organizing feature mapping - R. Der; M. Herrmann; T. Villmann (Biological Cybernetics, 1997)

A neural model of the dynamic activation of memory - M. Herrmann; E. Ruppin; M. Usher (Biological Cybernetics, 1993)

Immunological characterization of the Marin County strain of astrovirus - J. E. Herrmann; W. D. Cubitt; R. W. Hudson; Dorothy M. Perron-Henry; L. S. Oshiro; N. R. Blacklow (Archives of Virology, 1990)

Preparation and characterization of monoclonal antibodies to enteric adenovirus types 40 and 41 - J. E. Herrmann; Dorothy M. Perron-Henry; Darlene Stobbs-Walro; N. R. Blacklow (Archives of Virology, 1987)

Results of chromosome analysis of rabies virus infected human diploid cells (WI-38) - M. Majer; Annelies Herrmann; R. Mauler (Archives of Virology, 1977)

Sublimat-Vergiftung - M. Herrmann (Archives of Toxicology, 1937)